Assessment of Evaluation Tools for Integrated Surveillance of Antimicrobial Use and Resistance Based on Selected Case Studies - Sandberg, Marianne; Hesp, Ayla; Aenishaenslin, Cécile; Bordier, Marion; Bennani, Houda; Bergwerff, Ursula; Chantziaras, Ilias; De Meneghi, Daniele; Ellis-Iversen, Johanne; Filippizi, Maria-Eleni; Mintiens, Koen; Nielsen, Liza R.; et al. (Frontiers in Veterinary Science, 2021)
Regular evaluation of integrated surveillance for antimicrobial use (AMU) and resistance (AMR) in animals and humans is needed to ensure system effectiveness, but the question is how. In this study, six different evaluation tools were assessed after being applied to AMU/AMR surveillance in eight countries: 1) AMR-ISS: AMR Integrated Surveillance Systems, 2) ECoSur: Evaluation of Collaboration for Surveillance, 3) FAO- ATLASS: the Assessment Tool for Laboratories and AMR Surveillance Systems developed by FAO, 4) FAO-PMP-AMR The Progressive Management Pathway tool on AMR developed by the Food and Agriculture Organization (FAO) of United Nations, 5) NEOH: developed by the EU COST Action ‘Network for Evaluation of One Health’ and 6) SURVTOOLS: developed in the FP7-EU project ‘RISKSUR’. Each tool was scored using i) 11 pre-defined functional aspects (e.g., workability concerning the need for data, time and people), ii) a SWOT-like approach of user experiences (e.g., things that I liked, or that the tool covered well), and iii) eight predefined content themes related to coverage (e.g., development purpose, collaboration). The FAO-PMP-AMR, ATLASS, ECoSur and NEOH are evaluation tools that provide a scoring system to obtain semi-quantitative results, whereas AMR-ISS and SURVTOOLS will result in a plan for how to conduct evaluation(s). AMR-ISS, ECoSur, NEOH and SURVTOOLS allow for in-depth analyses and therefore require more complex data, information and specific training of evaluator(s). FAO-PMP-AMR, ATLASS and AMR-ISS were developed specifically for AMR-related activities. NEOH and AMR-ISS were perceived as the best tools for evaluation of broader OH aspects, and ECoSur and AMR-ISS as best for evaluation of the quality of collaboration. FAO-PMP-AMR and FAO-ATLASS seemed to be the most user-friendly tools, particularly designed for risk managers. FAO-ATLASS was the only tool focusing specifically on laboratory activities. Only AMR-ISS included production of a direct measure for the “integration” and “impact on decision-making”. Our experience is that adequate resources are needed to perform evaluation(s). In most cases, evaluation would require involvement of several assessors and/or stakeholders, taking from weeks to months to complete. This study can help direct future evaluators of integrated AMU/AMR surveillance towards the most adequate tool for their specific evaluation purpose.